Improving electron microscopy with light - Hommelhoff, Peter (Nature Photonics, 2025)
Shining intense laser pulses on an electron beam in an electron microscope corrects electron-optical spherical aberration, paving the way to using light to improve electron microscopy imaging.
CRIS-Team Scopus Importer:2025-12-12